2009
DOI: 10.1097/pcc.0b013e31819368ca
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasound-guided radial artery cannulation in children

Abstract: US guidance did not facilitate faster cannulation of the radial artery in children in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 11 publications
2
98
1
Order By: Relevance
“…Shiver et al (14) showed in 60 critically ill emergency room patients an improvement in first-pass success rate from 50% to 87% (p ¼ 0.005) and a reduction in time from 314 s versus 107 s (p ¼ 0.0004). In 1 trial, US did not have a benefit, which was felt by the investigators to be due to insufficient experience, with 94% of operators having <5 US-guided procedures (15). These findings are summarized in a meta-analysis, which suggested a 17% absolute improvement (26% to 43%) in firstpass success rate (10).…”
Section: Methodsmentioning
confidence: 97%
“…Shiver et al (14) showed in 60 critically ill emergency room patients an improvement in first-pass success rate from 50% to 87% (p ¼ 0.005) and a reduction in time from 314 s versus 107 s (p ¼ 0.0004). In 1 trial, US did not have a benefit, which was felt by the investigators to be due to insufficient experience, with 94% of operators having <5 US-guided procedures (15). These findings are summarized in a meta-analysis, which suggested a 17% absolute improvement (26% to 43%) in firstpass success rate (10).…”
Section: Methodsmentioning
confidence: 97%
“…15 On the other hand, in another prospective trial involving 152 children by Ganesh et al, US guidance did not facilitate faster cannulation of the radial artery. 24 A possible explanation for this may again relate to operator inexperience. It was noted in the article that experienced operators (supervising consultant anesthesiologists) were successful where an initial inexperienced operator failed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended to use ultrasound-guided arterial catheterization routinely in these patients. The experience gained by using ultrasound routinely will be very beneficial in difficult or extreme cases [57].…”
Section: Integration In Clinical Practicementioning
confidence: 99%